Secondary batteries and electrical devices
By adjusting the redox reaction characteristics of the positive electrode active material in lithium manganese iron phosphate batteries, the problem of poor circulation and storage performance of the battery under high temperature conditions is solved, and excellent high-temperature circulation and storage performance are achieved.
Patent Information
- Application Number
- CN202411641270.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing lithium manganese iron phosphate batteries have poor circulation and storage performance under high temperature conditions, resulting in rapid capacity decay.
By controlling the redox reaction characteristics of the positive electrode active material in the secondary battery, the specific method is to reasonably adjust the mass ratio and molar content of manganese element of the first lithium manganese iron phosphate and the second lithium manganese iron phosphate in the positive electrode active material layer. The peak difference value (△V) and half-maximum width (W) of peak A and peak B make them satisfy a specific relationship to optimize the thermodynamic barrier and reaction kinetics of the redox platform.
The excellent cycle characteristics and storage performance of the secondary battery under high temperature conditions are achieved, extending the cycle life of the battery and maintaining efficient energy storage.
Smart Images

Figure CN119153685B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, in particular to a secondary battery and an electrical device. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP) is a battery cathode material widely used in electric vehicles and energy storage devices, but its energy density is relatively low. As an upgraded product of lithium iron phosphate, lithium iron manganese phosphate has improved energy density. The theoretical voltage platform of lithium iron phosphate is about 3.5V. With the introduction of manganese, the charge and discharge voltages of manganese and iron are different. There are two voltage platforms for the charge and discharge of lithium iron manganese phosphate, corresponding to the redox of manganese and iron. The platform near 3.5V is Fe 2+ Converted to Fe 3+ , around 4.1V corresponds to Mn 2+ Converted to Mn 3+ That is, the introduction of manganese elements enables the voltage platform of lithium manganese iron phosphate to reach 4.1V, and the theoretical energy density is increased by 10~20% compared with lithium iron phosphate, which helps to improve the cruising range of new energy vehicles.
[0003] For batteries with lithium manganese iron phosphate (LMFP) as the positive electrode active material, the operating voltage of the battery changes as the battery fails during cycling or storage, and the active lithium is consumed. The cutoff potential of the negative electrode rises sharply, which causes the battery to reach the discharge cutoff voltage in advance when the positive electrode potential is high during the discharge process of the battery. This makes it impossible to fully utilize the capacity of the iron platform, resulting in a significant reduction in the actual available capacity of the battery during the discharge process, and the capacity of the LMFP system battery cell decays rapidly.
[0004] Under high temperature conditions, the rates of various side reactions inside the battery increase, the active lithium will be consumed at a faster rate, and high temperature will aggravate the structural degradation of the electrode material, resulting in a faster capacity decay rate of the LMFP battery and relatively poor high temperature cycle performance of the battery.
[0005] It has been reported in the prior art that a certain amount of lithium iron phosphate (LFP) is mixed into LMFP to improve the active lithium consumption rate, but the mixing of LFP leads to a decrease in the high-temperature storage performance of the battery and also affects the kinetic performance.
[0006] Therefore, it is necessary to develop a secondary battery with good high temperature cycle performance and high temperature storage performance. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a secondary battery and an electrical device. By controlling the redox reaction characteristics of the positive electrode active material in the secondary battery, the secondary battery of the present invention has excellent high-temperature cycle characteristics and high-temperature storage performance.
[0008] To achieve the above object, in a first aspect of the present invention, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium manganese iron phosphate material;
[0009] The secondary battery is charged and discharged at 45°C under the condition of 1C / 1C, and the charge and discharge curve is differentiated to plot a dQ / dV-V graph with the voltage value as the horizontal axis and the capacity-voltage differential value as the vertical axis; the dQ / dV-V graph has two main reduction peaks with different potentials in the range of 3.0V to 3.85V, wherein the main reduction peak with a lower potential is peak A, and the peak position value of peak A is V A The main reduction peak with a higher potential is peak B, and the peak position of peak B is V B ;
[0010] The half-peak width of peak A is recorded as W;
[0011] The peak position difference between peak A and peak B is recorded as △V, △V = V B -V A ;
[0012] △V and W satisfy the following relationship:
[0013] 0.011≤△V 0.2 ×W≤0.145;
[0014] The V A 、V B The unit of , △V and W is V.
[0015] As a preferred embodiment of the present invention, ΔV and W satisfy the following relationship: 0.015≤ΔV 0.2 ×W≤0.11.
[0016] As a preferred embodiment of the present invention, the range of ΔV is 0.05~0.3V.
[0017] As a further preferred embodiment of the present invention, the range of ΔV is 0.08~0.27V.
[0018] As a preferred embodiment of the present invention, the range of W is 0.016~0.20V.
[0019] As a further preferred embodiment of the present invention, the range of W is 0.022~0.15V.
[0020] As a preferred embodiment of the present invention, the positive electrode active material includes a first lithium iron manganese phosphate and a second lithium iron manganese phosphate, and the molar content of manganese in the first lithium iron manganese phosphate is greater than the molar content of manganese in the second lithium iron manganese phosphate.
[0021] As a preferred embodiment of the present invention, the molar content of manganese element in the first lithium manganese iron phosphate is 60-90%.
[0022] As a preferred embodiment of the present invention, the molar content of manganese element in the second lithium manganese iron phosphate is 0.05-25%.
[0023] As a preferred embodiment of the present invention, the mass ratio of the first lithium manganese iron phosphate to the second lithium manganese iron phosphate is (2.3-9):1.
[0024] In a second aspect of the present invention, the present invention provides an electrical device comprising the secondary battery described above.
[0025] The beneficial effects of the present invention are:
[0026] The present invention provides a secondary battery and an electric device. The present invention controls the redox reaction characteristics of the positive electrode active material in the secondary battery so that the secondary battery has excellent high-temperature cycle characteristics and high-temperature storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 dQ / dV-V diagram of the lithium ion battery of Example 2. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0030] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0031] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0032] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0033] An embodiment of the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium manganese iron phosphate material;
[0034] The secondary battery is charged and discharged at 45°C under the condition of 1C / 1C, and the charge and discharge curve is differentiated to plot a dQ / dV-V graph with the voltage value as the horizontal axis and the capacity-voltage differential value as the vertical axis; the dQ / dV-V graph has two main reduction peaks with different potentials in the range of 3.0V to 3.85V, wherein the main reduction peak with a lower potential is peak A, and the peak position value of peak A is V A The main reduction peak with a higher potential is peak B, and the peak position of peak B is V B ;
[0035] The half-peak width of peak A is recorded as W;
[0036] The peak position difference between peak A and peak B is recorded as △V, △V = V B -V A ;
[0037] △V and W satisfy the following relationship:
[0038] 0.011≤△V 0.2 ×W≤0.145;
[0039] The V A 、V B The units of , △V and W are all volts (V).
[0040] In the present invention, by controlling the redox reaction characteristics of the positive electrode active material, the secondary battery has excellent high-temperature cycle characteristics and high-temperature storage performance.
[0041] In the dQ / dV-V diagram, the voltage peak represents a significant redox reaction at a specific voltage. There are two main reduction peaks in the range of 3.0V to 3.85V, which indicates that the positive electrode active material of the present invention has two main electrochemical reactions in this voltage range and has at least two Fe reduction reaction platforms with different potentials. In the present invention, △V represents the peak position difference of the two main reduction peaks with the lowest potential in the dQ / dV-V diagram in the order of potential from low to high, which reflects the Fe reduction reaction in the positive electrode active material. 3+ The potential difference when reduced; W represents the half-peak width of peak A, that is, the half-peak width of the main reduction peak with the lowest potential, which indirectly reflects the platform slope of the low-potential Fe reaction platform and reflects the kinetic performance of the battery.
[0042] The present invention has found that △V and W should be comprehensively controlled to satisfy |△V| 0.2 ×W ranges from 0.011 to 0.145. By comprehensively adjusting △V and W, comprehensively regulating the thermodynamic barrier and reaction kinetics of the redox platform, introducing a low-potential Fe reaction platform, and controlling the platform potential and platform slope of the low-potential Fe reaction, the intersection of the low-potential Fe platform and the negative electrode discharge cut-off potential is later, the positive electrode capacity can be fully released, and the high-temperature cycle performance of the battery can be effectively improved, and the high-temperature storage performance remains high.
[0043] When △V 0.2 When the value of ×W is lower than 0.011, it may mean that the manganese content in the positive electrode active material is too high, or the kinetic performance is better. During the high-temperature cycle of the battery, the high manganese content may lead to more manganese dissolution in the positive electrode, and the high kinetic performance may lead to high-activity interface side reactions, resulting in active lithium loss and impedance growth, resulting in poor high-temperature cycle performance of the battery. When △V 0.2 When the value of ×W is higher than 0.145, the intersection of the low-potential Fe platform and the negative electrode discharge cut-off potential will be closer to the front, the overall battery voltage will reach its cut-off voltage too early, the positive electrode voltage window will be narrowed, and the capacity of the positive electrode active material will not be fully utilized, the actual capacity will be reduced, and under high temperature conditions, the active lithium will be consumed faster, resulting in rapid attenuation of the battery capacity and a significant decrease in high-temperature cycle performance. In addition, when △V 0.2 When the value of ×W is too high, the high temperature storage performance of the battery will be seriously degraded. A certain degree of manganese dissolution can help the negative electrode form a more stable SEI film; 0.2 When ×W is too high, the initial interaction between the positive electrode and the negative electrode is small, and the negative electrode film formation stability is poor. During high-temperature storage, the SEI film continues to crack and repair, but consumes a large amount of active lithium and electrolyte, resulting in degradation of the battery's high-temperature storage performance.
[0044] The electrochemical reaction in the battery is nonlinear, and the electrochemical reactions on different platforms affect each other. By introducing the 0.2 power of △V, the interference between different reduction reactions is balanced, so that △V 0.2 ×W relationship can more accurately reflect the actual kinetic characteristics, thereby more accurately describing the mutual influence between different voltage platforms to achieve the high-temperature cycle characteristics and high-temperature storage performance of the battery.
[0045] Exemplarily, in the present invention, ΔV 0.2 The value of ×W can be 0.011, 0.020, 0.025, 0.030, 0.040, 0.045, 0.050, 0.060, 0.070, 0.080, 0.085, 0.090, 0.095, 0.145, or it can be an interval formed by any two of the above values.
[0046] In one preferred embodiment, ΔV and W satisfy the following relationship: 0.015≤ΔV 0.2 ×W≤0.11.
[0047] △V 0.2 When ×W satisfies the above preferred range, the battery has better high-temperature cycle performance and high-temperature storage performance.
[0048] In one preferred embodiment, the range of ΔV is 0.05-0.3V. For example, the ΔV may be 0.05V, 0.10V, 0.15V, 0.20V, 0.25V, 0.28V, or 0.30V.
[0049] In a more preferred embodiment, the range of ΔV is 0.08-0.27V.
[0050] The value of △V should not be too high or too low. When △V is 0.05~0.3V, preferably 0.08~0.27V, the overall electrochemical performance of the battery is optimized, the high-temperature cycle capacity retention rate is better, and the high-temperature storage performance is higher. The present invention has found that when the value of △V is small, the potential of the introduced low-potential Fe reaction platform is higher, so that the reaction energies of the two Fe platforms in the positive electrode active material are closer, which is conducive to the intersection of the low-potential Fe platform and the negative electrode discharge cut-off potential being later, the positive electrode capacity can be fully released, and the battery high-temperature cycle capacity retention rate is improved. At the same time, the value of △V is not easy to be too small. When the △V value is too small, the manganese dissolution of the positive electrode active material increases, the failure reaction of the high-temperature cycle is violent, the active lithium loss is large, and the high-temperature cycle performance decreases.
[0051] In one preferred embodiment, the range of W is 0.016~0.2V. For example, W can be 0.016V, 0.02V, 0.05V, 0.08V, 0.10V, 0.12V, or 0.2V.
[0052] In a more preferred embodiment, the range of W is 0.022~0.15V.
[0053] When W is within the above preferred range, it reflects that the half-peak width of peak A is in a suitable range, and within the reduction reaction interval, the voltage change rate is appropriate, the battery kinetics is good, and it will not cause too many interface side reactions, and the battery's high-temperature cycle and high-temperature storage performance are both excellent. When the value of W is too large, the greater the half-peak width of peak A, it means that within the reduction reaction interval, the voltage changes faster, and the slope of the reduction reaction platform is also larger, which may cause the battery to drop to a lower voltage before fully utilizing its capacity, and reach the discharge cut-off voltage in advance; it also means that the voltage range for the reduction reaction is wider, indicating that the reaction rate is slower and the reduction reaction kinetics is poor. When the value of W is too small, it means that there are relatively more interfacial active sites in the positive electrode active material, which may lead to serious positive electrode interface side reactions, and it is also not conducive to assisting the negative electrode to form a more stable SEI film through interaction, thereby making the battery's high-temperature cycle and high-temperature storage performance relatively poor.
[0054] The values of △V and W are affected by many factors of the positive electrode active material, such as the manganese content in the lithium manganese iron phosphate material, the particle size of the positive electrode active material, the carbon coating condition and the processing technology.
[0055] The present invention does not limit the detection method of ΔV and W. Those skilled in the art can perform charge and discharge tests on the secondary battery at 45° C. at 1C / 1C conditions according to conventional technical means, draw a dQ / dV-V curve, and obtain ΔV and W.
[0056] Exemplarily, the detection method of ΔV and W can be performed by the following method:
[0057] (1) High temperature constant capacity: the secondary battery using the positive electrode sheet is left at rest for 120 min at 45°C, and discharged at 1C constant current to 2.5V; after leaving at rest for 20 min, it is charged at 1C constant current and constant voltage to a cut-off voltage of 4.25V and a cut-off current of 0.33C; after leaving at rest for 20 min, it is discharged at 1C constant current to 2.5V; the constant capacity is terminated, and the charge and discharge curve is obtained;
[0058] (2) Drawing a dQ / dV-V curve: Based on the above charge and discharge curve, the voltage and charge data of the nth data point are subtracted from the voltage and charge data of the n+1th data point to obtain a dV and dQ data; all the data are processed in sequence to obtain a series of dV and dQ data; then dQ is divided by dV to obtain dQ / dV; the capacity-voltage differential value (dQ / dV) is used as the ordinate and the voltage value is used as the abscissa to obtain a dQ / dV-V curve;
[0059] (3) In the order of potential from low to high, in the range of 3.0 V to 3.85 V in the dQ / dV-V diagram, the main reduction peak at the lower potential is Peak A, and the peak value of Peak A is V A The main reduction peak with a higher potential is peak B, and the peak position of peak B is V B ; The peak position difference between peak A and peak B is recorded as △V, △V = V B -V A ;
[0060] The half-width of peak A is W;
[0061] V A 、V B The units of , △V and W are all volts (V).
[0062] The peaks in the dQ / dV-V graph correspond to Fe reduction reaction platforms at different potentials. When the capacity utilization interval corresponding to the Fe reduction reaction platform is in different phase change regions of the negative electrode material, it may cause the splitting of the reduction peak in the dQ / dV-V graph (a phenomenon where a peak splits into two or more peaks), resulting in multiple split peaks. When multiple split peaks appear in the dQ / dV-V graph, the peak with the highest peak intensity in the group of peaks is the main reduction peak.
[0063] In one preferred embodiment, the positive electrode active material includes a first lithium iron manganese phosphate and a second lithium iron manganese phosphate, and the molar content of manganese in the first lithium iron manganese phosphate is greater than the molar content of manganese in the second lithium iron manganese phosphate.
[0064] The molar content of manganese in the first lithium manganese iron phosphate is the molar content of manganese in the first lithium manganese iron phosphate to other metal elements except lithium. The molar content of manganese in the second lithium manganese iron phosphate is the molar content of manganese in the second lithium manganese iron phosphate to other metal elements except lithium.
[0065] The lithium iron manganese phosphate materials with high manganese and low manganese content are used. The Fe content in the two lithium iron manganese phosphate materials with different manganese contents is 3+ -Fe 2+ The reaction potential is different, so that the introduction of the low-potential Fe platform can be well achieved, and ΔV and W can be controlled to satisfy the above relationship range.
[0066] In one preferred embodiment, the molar content of manganese in the first lithium manganese iron phosphate is 60-90%.
[0067] In a more preferred embodiment, the molar content of manganese in the first lithium manganese iron phosphate is 75-85%.
[0068] In one preferred embodiment, the molar content of manganese in the second lithium manganese iron phosphate is 0.05-25%.
[0069] In a more preferred embodiment, the molar content of manganese in the second lithium manganese iron phosphate is 0.1-10%.
[0070] The first lithium manganese iron phosphate is a lithium manganese iron phosphate material with a high manganese content, and the second lithium manganese iron phosphate is a lithium manganese iron phosphate material with a low manganese content. The lithium manganese iron phosphate material with a high manganese content can achieve appropriate manganese dissolution in the positive electrode active material, which helps to make the negative electrode SEI film more stable and the battery has better high-temperature storage performance. The lithium manganese iron phosphate material with a low manganese content mainly plays the role of a low-potential Fe platform, providing capacity contribution to a lower voltage platform. The introduction of an appropriate lithium manganese iron phosphate material with a low manganese content can effectively balance the potential difference between the high and low potential platforms, so that the △V value is within an appropriate range.
[0071] When the manganese content of the first lithium manganese iron phosphate and the second lithium manganese iron phosphate exceeds the above preferred range, it may be insufficient to improve the loss of lithium ions, resulting in slightly poor high-temperature cycle performance of the battery; or it may be difficult to promote the stability of the negative electrode SEI film, resulting in poor high-temperature storage performance of the battery.
[0072] The present invention does not limit the method for detecting the manganese content, and those skilled in the art can detect the manganese content of lithium iron manganese phosphate materials according to conventional technical means.
[0073] Exemplarily, the molar content of manganese in the lithium manganese iron phosphate can be detected by the following method:
[0074] The battery is disassembled to obtain the positive electrode sheet, which is then processed to obtain the positive electrode active material powder. The molar content of manganese element in the first lithium manganese iron phosphate and the second lithium manganese iron phosphate is obtained through scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) testing.
[0075] In one preferred embodiment, the mass ratio of the first lithium manganese iron phosphate to the second lithium manganese iron phosphate is (2.3-9):1.
[0076] In a more preferred embodiment, the mass ratio of the first lithium manganese iron phosphate to the second lithium manganese iron phosphate is (4-7):1.
[0077] When the mass ratio of the first lithium manganese iron phosphate to the second lithium manganese iron phosphate is within an appropriate range, the balance between the high temperature storage performance and the high temperature cycle performance of the battery is better, and the overall electrochemical performance is excellent. When the mass ratio of the first lithium manganese iron phosphate to the second lithium manganese iron phosphate exceeds the above preferred range, the electrode material may deteriorate more seriously at high temperature due to the poor adaptability of the high and low manganese ratios, resulting in a slight decrease in the high temperature performance of the battery.
[0078] In particular, when the mass proportion of the second lithium manganese iron phosphate is too high, it may lead to insufficient charging capacity at high SOC, increase stress and side reactions inside the battery, accelerate degradation of electrode materials under high temperature conditions, and shorten the high-temperature cycle performance of the battery. In addition, under high-temperature storage conditions, the electrochemical reaction rate inside the battery is accelerated, and the active lithium in the battery may be consumed due to self-discharge reactions or electrolyte decomposition, causing the negative electrode potential to rise and the positive electrode potential to drop. The changes in the positive and negative electrode potentials cause the battery cutoff potential to change. When the mass proportion of the second lithium manganese iron phosphate is too high, when the battery reaches the cutoff potential, there may be a large amount of the second lithium manganese iron phosphate that has not yet participated in the electrochemical reaction and failed to contribute to the actual capacity of the battery, resulting in poor high-temperature storage performance of the battery.
[0079] The present invention does not limit the method for detecting the mass ratio of the first lithium iron manganese phosphate and the second lithium iron manganese phosphate in the positive electrode active material of the positive electrode plate.
[0080] Exemplarily, the mass ratio of the first lithium manganese iron phosphate and the second lithium manganese iron phosphate in the positive electrode active material of the positive electrode plate can be detected by the following method:
[0081] The secondary battery containing the positive electrode plate is discharged to 2V at 0.33C at room temperature, then charged to 4.25V at 0.33C constant current, charged to 0.05C at constant voltage, and discharged to 2.5V at 0.33C constant current, and the cycle is repeated for 2 weeks. The discharge data of the last week are plotted as a voltage-capacity curve, and the mass ratio of the first lithium manganese iron phosphate and the second lithium manganese iron phosphate with different manganese contents is determined according to the ratio of the manganese platform to the iron platform.
[0082] In one preferred embodiment, the surface of the second lithium manganese iron phosphate is coated with a carbon material, and the mass ratio of the carbon material to the second lithium manganese iron phosphate (recorded as the carbon coating amount) is 1.0-3.0 wt.%.
[0083] The present invention does not limit the method for detecting the carbon coating amount, and those skilled in the art can detect the carbon coating amount of the positive electrode active material according to conventional technical means.
[0084] Exemplarily, the carbon coating amount can be tested by the following method:
[0085] After being weighed by an electronic balance, the sample enters the combustion reaction pool. Under the condition of sufficient oxygen, it is heated and burned at high temperature by a high-frequency furnace to oxidize carbon into carbon dioxide. After filtering and drying, the gas enters the corresponding absorption pool to absorb the corresponding infrared radiation spectrum (carbon dioxide 4200nm), and then converted into a corresponding electrical signal by the detector. This signal is collected by a computer, converted into a value proportional to carbon dioxide after linear correction, and then the values of the entire analysis process are accumulated. After the analysis is completed, the accumulated value is divided by the weighing value in the computer, and then multiplied by the correction coefficient to obtain the mass fraction of carbon in the sample.
[0086] In the present invention, the preparation method of lithium manganese iron phosphate is not limited, and those skilled in the art can prepare it according to conventional technical means.
[0087] Exemplarily, the preparation method of lithium manganese iron phosphate may include the following steps:
[0088] Mixing a manganese source, an iron source, a phosphorus source, a lithium source and a carbon source (if any) in a certain molar ratio, and ball milling and spray drying;
[0089] The spray-dried product is sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0090] The sintered material is crushed and screened to obtain LMFP.
[0091] The lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.
[0092] The phosphorus source may include at least one of diammonium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate, or lithium phosphate.
[0093] The iron source may include at least one of ferrous oxalate, ferric hydroxide, ferrous hydroxide, ferric phosphate, ferrous phosphate, ferric acetate, ferrous acetate, ferric carbonate, ferrous carbonate, ferrous oxide, ferrous oxide or ferric oxalate.
[0094] The manganese source may include at least one of manganese carbonate, manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, or manganese acetate.
[0095] The carbon source may include glucose.
[0096] The LMFP of the present invention may contain a certain amount of doping elements. Optionally, the doping element may be selected from at least one of Mg, Ca, Sr, Ti, V, Cr, Ni, Co, Rb, Cu, Zn, La, Y, Mo, Nb, Al, and W.
[0097] When the LMFP contains a doping element, a certain amount of a doping element source such as a vanadium source (vanadium pentoxide), a tungsten source (ammonium metatungstate), a titanium source (titanium oxide), a magnesium source (magnesium carbonate), etc. can be mixed with a manganese source, an iron source, a phosphorus source, a lithium source, etc. as needed during the preparation of the LMFP to obtain a LMFP containing a certain amount of the doping element.
[0098] The chemical formula of lithium iron manganese phosphate is: LiMn x Fe y M z n PO4, wherein x is greater than 0 and less than 1; y is greater than 0 and less than 1; z is greater than or equal to 0 and less than 1; M refers to the doping element, and n refers to the valence of the doping element; and satisfies: 2(x+y)+n×z=2.
[0099] Ferromanganese phosphate can be selected as a manganese source, an iron source and a phosphorus source at the same time; ferric phosphate can be selected as a manganese source, an iron source and a phosphorus source at the same time; the lithium source can include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.
[0100] The ball milling and spray drying can be repeated multiple times. Exemplarily, the steps of mixing the manganese source, iron source, phosphorus source, lithium source and carbon source (if any) in a certain molar ratio, and performing ball milling and spray drying can include the following:
[0101] A manganese source, an iron source, a phosphorus source, and a lithium source are mixed in a certain molar ratio, and a first ball milling is performed, and a first spray drying is performed after the first ball milling;
[0102] The product after the first spray drying is mixed with a carbon source (if any), and a second ball milling is performed, and then a second spray drying is performed after the second ball milling.
[0103] The first ball milling, the second ball milling, the first spray drying, and the second spray drying can all adopt different process conditions.
[0104] Optionally, the sintering may adopt gradient sintering conditions.
[0105] By adjusting the addition amount of manganese source, iron source and phosphoric acid, the proportion of manganese content in LMFP can be controlled.
[0106] By adjusting the amount of carbon source added, the proportion of carbon coating can be controlled.
[0107] In addition to the above-mentioned positive electrode active material, the positive electrode active material layer may further include a conductive agent and a binder.
[0108] The conductive agent can be used as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. In the present invention, there is no particular limitation on the type of the conductive agent. Specifically, the conductive agent can be at least one of carbon nanotubes, carbon black or graphene.
[0109] The binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. Specifically, the conductive agent can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.
[0110] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.
[0111] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art, for example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent to form a uniform positive electrode slurry, the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.
[0112] An embodiment of the present invention provides a secondary battery, comprising the positive electrode sheet described above.
[0113] In addition to the positive electrode plate, the secondary battery also includes a negative electrode plate, a separator and an electrolyte.
[0114] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material. For the negative electrode active material, the embodiment of the present invention does not specifically limit the type of the negative electrode active material, and can be selected according to actual needs. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, and silicon-carbon composites.
[0115] The diaphragm is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm can be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.
[0116] The electrolyte of the present invention can be any electrolyte suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt.
[0117] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5-5 mol / L.
[0118] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0119] An embodiment of the present invention provides an electric device, comprising the secondary battery described above.
[0120] The electrical device serves as a power supply for the electrical device.
[0121] The electrical device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other energy forms, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0122] The present invention is further described below with reference to specific embodiments.
[0123] Example 1
[0124] Embodiment 1 provides a lithium ion battery, and the preparation method is as follows:
[0125] (1) Preparation of positive electrode
[0126] (1.1) Preparation of positive electrode active materials
[0127] Preparation of the first lithium manganese iron phosphate:
[0128] According to the target chemical formula LiMn x1 Fe 1-x1 The molar ratios of Li, Mn, Fe, and P in PO4 (where x1 is shown in Table 1) were as follows: lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate were weighed and mixed, and then ball milled (speed 120 rpm, time 5 h);
[0129] The ball-milled slurry was spray-dried (spraying temperature 220°C, time 1h);
[0130] The spray-dried product is placed in a high-temperature tube furnace, high-purity nitrogen is introduced into the high-temperature tube furnace, vacuumized, calcined at 700° C. for 5 hours, and cooled to room temperature to obtain a first lithium manganese iron phosphate precursor;
[0131] The carbon source (glucose) and the first lithium manganese iron phosphate precursor are mixed, and the amount of the carbon source added is 7% of the weight of the first lithium manganese iron phosphate precursor; and then ball milling is performed again (rotating speed is 120 rpm, time is 5 hours);
[0132] The ball-milled slurry is spray-dried;
[0133] The spray-dried product was placed in a high-temperature tube furnace, high-purity nitrogen was introduced into the high-temperature tube furnace, vacuum was drawn, calcined at 650° C. for 6 hours, and cooled to room temperature; the first lithium manganese iron phosphate was obtained.
[0134] Preparation of the Second Lithium Manganese Iron Phosphate:
[0135] S1. According to the target chemical formula LiMn x2 Fe 1-x2 The molar ratios of Li, Mn, Fe, and P in PO4 (where x2 is shown in Table 1), FePO4, LiOH, NH4H2PO4, and MnSO4 are weighed, where the molar ratio of FePO4 to LiOH is 1:1, and a certain amount of glucose is weighed;
[0136] S2. FePO4 and LiOH were mixed and ball-milled for the first time at 130 rpm for t1 min, and the slurry after ball milling was spray-dried for the first time (spraying temperature 220°C, time 1h); NH4H2PO4 was added and ball-milled for the second time at 130 rpm for t2 min, and the slurry after ball milling was spray-dried for the second time (spraying temperature 200°C, time 1.5h); then MnSO4 and glucose were added and ball-milled for the third time at 130 rpm for t3 min, and the slurry after ball milling was spray-dried for the third time (spraying temperature 220°C, time 1.5h); wherein the amount of glucose added was adjusted so that the mass ratio of the carbon material coated on the surface of the second lithium manganese iron phosphate (carbon coating ratio) met the requirements shown in Table 1; t1, t2, and t3 were also as shown in Table 1;
[0137] S3. The product after the last spray drying in step S2 is placed in a high-temperature tube furnace, high-purity nitrogen is introduced into the high-temperature tube furnace, vacuumized, and sintered. The sintering conditions are: heating from 25°C at a rate of 5°C / min, keeping the temperature for 10 minutes every time the temperature rises by 100°C, and keeping the temperature for 6 hours after the temperature rises to T°C, where T is shown in Table 1;
[0138] S4. The sintered product is cooled to room temperature to obtain the second lithium manganese iron phosphate.
[0139] (1.2) mixing the first lithium manganese iron phosphate and the second lithium manganese iron phosphate uniformly according to the mass ratio shown in Table 1 to obtain a positive electrode active material;
[0140] The positive electrode active material is mixed with PVDF, SP, and CNT in a mass ratio of 97:1.5:1:0.5, and dispersed in NMP to obtain a positive electrode slurry. Subsequently, the mixed positive electrode slurry is evenly coated on an aluminum foil, dried in a vacuum oven at 100°C, rolled, cut, and baked to obtain a positive electrode sheet.
[0141] (2) Preparation of negative electrode
[0142] The negative electrode active material (artificial graphite), conductive agent (SP), and binder (carboxymethyl cellulose, CMC) are mixed in a mass ratio of 96.4:1:2.6 and dispersed in deionized water to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode collector (copper foil). The negative electrode collector coated with the negative electrode slurry is transferred to a vacuum environment in an oven for drying at 100°C, and then rolled, cut, and baked to obtain a negative electrode sheet.
[0143] (3) Preparation of electrolyte
[0144] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0145] (4) Preparation of diaphragm
[0146] Polyethylene (PE) diaphragm is used.
[0147] (5) Preparation of batteries
[0148] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0149] Examples 2 to 16 and Comparative Examples 1, 3, and 4
[0150] Examples 2 to 16 and Comparative Examples 1, 3, and 4 respectively provide a lithium ion battery, and the preparation method is basically the same as that of Example 1, except that in the preparation of the positive electrode active material:
[0151] In the target chemical formulas of the first lithium manganese iron phosphate and the second lithium manganese iron phosphate, x1 and x2 are as shown in Table 1;
[0152] In S2, the ball milling time t1, t2, and t3 of the second lithium manganese iron phosphate of Examples 2 to 6, Examples 8 to 15, and Comparative Examples 1, 3, and 4 are as shown in Table 1, and the mass ratio of the carbon material coated on the surface of the second lithium manganese iron phosphate (carbon coating ratio) is as shown in Table 1, and the remaining steps are the same as in Example 1;
[0153] In Example 7, step S2 in preparing the second lithium manganese iron phosphate is as follows:
[0154] FePO4, LiOH, NH4H2PO4 and MnSO4 were mixed and ball-milled for the first time at 130 rpm for t1 min, and the slurry after ball milling was spray-dried for the first time (spraying temperature 220°C, time 1 h); then glucose was added and ball-milled for the second time at 130 rpm for t2 min, and the slurry after ball milling was spray-dried for the second time (spraying temperature 220°C, time 1.5 h); wherein the amount of glucose added was adjusted so that the mass ratio (carbon coating ratio) of the carbon material coated on the surface of the second lithium manganese iron phosphate met the requirements shown in Table 1; t1 and t2 of Example 7 are shown in Table 1;
[0155] Example 16 Step S2 in preparing the second lithium manganese iron phosphate is as follows:
[0156] FePO4, LiOH and NH4H2PO4 were mixed and ball-milled for the first time at 130 rpm for t1 min, and the slurry after ball milling was spray-dried for the first time (spraying temperature 220°C, time 1 h); then MnSO4 and glucose were added and ball-milled for the second time at 130 rpm for t2 min, and the slurry after ball milling was spray-dried for the second time (spraying temperature 220°C, time 1.5 h); wherein the amount of glucose added was adjusted so that the mass ratio of the carbon material coated on the surface of the second lithium manganese iron phosphate (carbon coating ratio) met the requirements shown in Table 1; t1 and t2 of Example 16 are shown in Table 1;
[0157] In S3, the values of T in the sintering of the second lithium manganese iron phosphate of Examples 2 to 9, Examples 11 to 16 and Comparative Examples 1, 3, and 4 are shown in Table 1, and the remaining steps are the same as those of Example 1;
[0158] In Example 10, step S3 in preparing the second lithium manganese iron phosphate is as follows:
[0159] The product after the last spray drying in step S2 is placed in a high-temperature tube furnace, and high-purity nitrogen is introduced into the high-temperature tube furnace, and vacuum is sintered. The sintering conditions are: heating from 25°C at a rate of 5°C / min, and continuously heating to T°C, and then keeping the temperature for 9h, where T is shown in Table 1;
[0160] In step (1.2), the mass ratios of the first lithium manganese iron phosphate and the second lithium manganese iron phosphate in Examples 2 to 16 and Comparative Examples 1, 3, and 4 are shown in Table 1, and the remaining steps are the same as in Example 1. Comparative Example 2
[0161] Comparative Example 2 provides a lithium ion battery, the preparation method of which is basically the same as that of Example 1, except that:
[0162] The second lithium iron manganese phosphate is replaced by lithium iron phosphate (LiFePO4). The preparation method and steps of lithium iron phosphate are basically the same as those of the second lithium iron manganese phosphate in Example 1, except that:
[0163] The target chemical formula of lithium iron phosphate is LiFePO4, and no MnSO4 is added during preparation;
[0164] The ball milling times t1, t2, t3, carbon coating ratio, and T value during sintering during the preparation of lithium iron phosphate are shown in Table 1.
[0165] Then, the first lithium iron manganese phosphate same as that in Example 1 and the lithium iron phosphate prepared in Comparative Example 2 were uniformly mixed in a mass ratio of 8:2 to obtain a positive electrode active material.
[0166] Table 1
[0167]
[0168] The ΔV and W of the lithium ion batteries prepared in each embodiment and comparative example were measured, as shown in Table 2; and the high temperature cycle performance and high temperature storage performance of the lithium ion batteries were tested, and the test results are shown in Table 2; the test methods for the above items are as follows:
[0169] △V and W test method:
[0170] (1) High temperature constant capacity: The lithium-ion battery was left at 45°C for 120 min, and discharged at 1C constant current to 2.5 V; after leaving it at rest for 20 min, it was charged at 1C constant current and constant voltage to a cut-off voltage of 4.25 V and a cut-off current of 0.33 C; after leaving it at rest for 20 min, it was discharged at 1C constant current to 2.5 V; the constant capacity was terminated, and the charge and discharge curve was obtained;
[0171] (2) Drawing a dQ / dV-V curve: Based on the above charge and discharge curve, the voltage and charge data of the nth data point are subtracted from the voltage and charge data of the n+1th data point to obtain a dV and dQ data; all the data are processed in sequence to obtain a series of dV and dQ data; then dQ is divided by dV to obtain dQ / dV; the capacity-voltage differential value dQ / dV is used as the ordinate and the voltage is used as the abscissa to obtain a dQ / dV-V curve;
[0172] (3) In the order of potential from low to high, in the range of 3.0 V to 3.85 V in the dQ / dV-V diagram, the main reduction peak at the lower potential is Peak A, and the main reduction peak at the higher potential is Peak B; the peak position difference between Peak A and Peak B is △V, in V; the half-peak width of Peak A is W, in V.
[0173] Test method for high temperature cycle capacity retention rate:
[0174] The lithium-ion battery was left at rest for 120 min at 45°C, fully charged at 1C constant current and constant voltage, with a cut-off voltage of 4.25V and a cut-off current of 0.33C, left at rest for 20 min, and then discharged at 1C constant current to 2.5V; the above was one cycle. The above steps were repeated for a total of 100 cycles (100 circles) of charge and discharge, and the discharge capacity of the second circle (Q1) and the discharge capacity of the 100th circle (Q2) were recorded. The high-temperature cycle capacity retention rate = Q2 / Q1×100%.
[0175] Test method for high temperature storage capacity recovery rate:
[0176] The lithium-ion battery is discharged to 2.5V at a constant current of 0.33C, then charged to 4.25V at a constant current of 0.33C, charged to 0.05C with a constant voltage, and discharged to 2.5V at a constant current of 0.33C; the above steps are repeated for a total of 3 times of charge and discharge to obtain the third discharge capacity Q3; then the battery is charged to 4.25V at a constant current of 0.33C, and then charged to 0.05C with a constant voltage, at which point the battery is at 100% SOC, and the battery continues to be stored in this state;
[0177] After the battery was stored at 60°C and 100% SOC for 30 days, it was discharged at a constant current of 0.33C to 2.5V, then charged at a constant current of 0.33C to 4.25V, charged at a constant voltage to 0.05C cut-off charge, and discharged at a constant current of 0.33C to 2.5V. The above steps were repeated for a total of 3 times of charge and discharge to obtain the third discharge capacity Q4;
[0178] High temperature storage capacity recovery rate = Q4 / Q3×100%.
[0179] The test results of each embodiment and comparative example are shown in Table 2.
[0180] The dQ / dV-V curve of Example 2 is as follows: Figure 1 As shown. It can be seen that there are two main reduction peaks in the range of 3.0V to 3.85V, of which the main reduction peak with a lower potential on the left side is peak A, and the main reduction peak with a relatively higher potential on the right side is peak B. It should be noted that for peak A, there is a split peak, and the peak with the highest peak intensity in the group of peaks is the main reduction peak (as shown by the arrow).
[0181] Table 2
[0182]
[0183] According to the test results in Table 2, it can be seen that for secondary batteries when △V 0.2 When ×W satisfies the range of the present invention (0.011~0.145), as shown in the embodiments, the battery has excellent high-temperature cycle performance and high-temperature storage performance, and the capacity retention rate after 100 cycles at 45°C is ≥89.5%, and the capacity recovery rate after storage for 30 days at 60°C is ≥88.5%.
[0184] According to Examples 12 and 13, it can be seen that when △V 0.2 When the value of ×W further meets the range of 0.015~0.11, the high-temperature cycle performance and high-temperature storage performance of the battery are relatively better.
[0185] It can be seen from Examples 1 to 7 and Examples 8 to 11 that when the value of ΔV is in the range of 0.08 to 0.27, or the value of W is in the range of 0.022 to 0.15, the high-temperature cycle performance and high-temperature storage performance of the lithium-ion battery are better overall.
[0186] According to Comparative Examples 1 to 4, when △V 0.2 When ×W is too low or too high, the high-temperature cycle performance and high-temperature storage performance of the lithium-ion battery are poor, the high-temperature cycle capacity retention rate is no higher than 83%, and the high-temperature storage capacity recovery rate is no higher than 83.5%.
[0187] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, characterized in that: The positive electrode active material includes lithium iron manganese phosphate material; The secondary battery is charged and discharged at 45°C under the condition of 1C / 1C, and the charge and discharge curve is differentiated to plot a dQ / dV-V graph with the voltage value as the horizontal axis and the capacity-voltage differential value as the vertical axis; the dQ / dV-V graph has two main reduction peaks with different potentials in the range of 3.0V to 3.85V, wherein the main reduction peak with a lower potential is peak A, and the peak position value of peak A is V A The main reduction peak with a higher potential is peak B, and the peak position of peak B is V B ; The half-peak width of peak A is recorded as W; The peak position difference between peak A and peak B is recorded as △V, △V = V B -V A ; △V and W satisfy the following relationship: 0.011≤△V 0.2 ×W≤0.145; The V A 、V B The unit of , △V and W is V; The range of ΔV is 0.05-0.3V, and the range of W is 0.016-0.20V.
2. The secondary battery according to claim 1, characterized in that: The △V and W satisfy the following relationship: 0.015≤△V 0.2 ×W≤0.
11.
3. The secondary battery according to claim 1, characterized in that: The range of △V is 0.08~0.27V.
4. The secondary battery according to claim 1, characterized in that: The range of W is 0.022~0.15V.
5. The secondary battery according to claim 1, characterized in that: The positive electrode active material includes a first lithium iron manganese phosphate and a second lithium iron manganese phosphate, wherein the molar content of manganese in the first lithium iron manganese phosphate is greater than the molar content of manganese in the second lithium iron manganese phosphate.
6. The secondary battery according to claim 5, characterized in that: The molar content of manganese element in the first lithium manganese iron phosphate is 60-90%.
7. The secondary battery according to claim 5, characterized in that: The molar content of manganese in the second lithium manganese iron phosphate is 0.05-25%.
8. The secondary battery according to claim 5, characterized in that: The mass ratio of the first lithium manganese iron phosphate to the second lithium manganese iron phosphate is (2.3-9):
1.
9. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Battery
CN117117177A
Battery evaluation system, battery evaluation method, program, and recording medium
CN117471334A